2016
DOI: 10.1016/j.ecolind.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

A new index for assessing heavy metal contamination in sediments of the Beijing-Hangzhou Grand Canal (Zaozhuang Segment): A case study

Abstract: a b s t r a c tZaozhuang Segment of the Beijing-Hangzhou Grand Canal is an important water conveyance line on the eastern route of the South-North Water Transfer Project in China and its water environment condition can exert a significant influence on diversion water quality safety. This paper analyzed contents of five heavy metals such as Cd, Cu, Ni, Pb and Zn as well as their chemical forms in surface sediments in this region. Methods including Threshold Effects Level-Probable Effects Level (TEL-PEL), Risk A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…10 Metals present in the F1 fraction are considered to be more weakly bound to the sediments, being able to equilibrate with the aqueous phase and therefore become more readily available. 36,[40][41][42][43] In relation to the reducible fraction (F2), it can be observed that Ni, Co and Pb have a strong affinity with this fraction, which is also potentially available. On average, 37.2% of Ni, 36.1% of Co and 30.5% of Pb were found in this fraction, ranges of 9.5-88%, 14.1-54.4% and 15.1-51.5%, respectively, between sampling points (S1 to S13).…”
Section: Total Trace Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Metals present in the F1 fraction are considered to be more weakly bound to the sediments, being able to equilibrate with the aqueous phase and therefore become more readily available. 36,[40][41][42][43] In relation to the reducible fraction (F2), it can be observed that Ni, Co and Pb have a strong affinity with this fraction, which is also potentially available. On average, 37.2% of Ni, 36.1% of Co and 30.5% of Pb were found in this fraction, ranges of 9.5-88%, 14.1-54.4% and 15.1-51.5%, respectively, between sampling points (S1 to S13).…”
Section: Total Trace Elementsmentioning
confidence: 99%
“…Secondary minerals in the silt fraction containing Fe and Al hydroxides (Figure 2) present large surface adsorption areas, increasing the retention of trace elements in this fraction. 19,43 These adsorbed metals (linked to Fe-Mn oxides) have the potential to be transferred to the aquatic environment, by means of changes in the redox potential or pH of the medium. 11,13,44,45 In the oxidizable fraction (F3), relatively high values are observed for Cr and Cu.…”
Section: Total Trace Elementsmentioning
confidence: 99%
“…Physical and chemical analyzes of sediment samples as organic matter by incineration were performed according to Trindade (1980); granulometry, screening and desimeter, second ISO 13320 (2009), total phosphorus through spectrophotometry according to EPA 6010C (2007) and total organic nitrogen by KJEDHAL (APHA 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The TEL is the concentration below which adverse biological effects are expected to rarely occur, while the concentration above which adverse effects are expected to occur frequently is defined as the PEL (CCME 2001a). Recent studies demonstrate that both methodologies are valid and present similar results (Nasr et al 2014;He et al 2015;McQueen et al 2016;Zhuang et al 2016). Although these guidelines also emphasize the importance of evaluating pollutants other than metals, certain organic pollutants, for instance, are usually taken into account only when indirect evidence has previously indicated their potential presence in a target aquatic system, i.e., certain pesticides in water bodies located near agricultural areas (CCME 1995).…”
mentioning
confidence: 99%
“…uncertainty of the health risk model. The principles of these methods differ, and each method has its own strengths and weaknesses [26,28].…”
Section: Introductionmentioning
confidence: 99%